Cytochrome P450 2C19 gene polymorphisms (CYP2C19*2 and CYP2C19*3) in chronic myeloid leukemia patients: in vitro and in silico studies. Issue 19 (15th November 2022) - Joshi, Kaishiv; Kaur, Satbir; Kumar, Rakesh
Abstract: Polymorphisms in the CYP2C19 have a huge impact on drug processing, out of which CYP2C19*2 and CYP2C19*3 are the most common variants associated with reduced metabolism of drugs. Mechanism by which two variants contribute in poor metabolization of drugs and cancer is not well understood. Here, we hypothesized that the mutations in CYP2C19 gene might affect the risk of chronic myeloid leukemia patients (CML). Present study has two main objectives: first to investigate the allele frequencies of CYP2C19*2 and CYP2C19*3 associated gene polymorphisms in CML patients and to elucidate the structural stability, conformation and functions of protein encoded by such variants. Genotyping of CYP2C19 was performed in 103 CML patients and 103 matched healthy controls. Heterozygous genotype of CYP2C19*2 was higher in CML patients (13.59%) than the controls (4.85%). Whereas, CYP2C19*3 allele frequency was not observed in cases as well as in controls. Furthermore, molecular dynamics (MD) simulation was applied to monitor the structural and conformational effect of above mutants. MD simulation results demonstrated that these mutants formed unstable proteins with distorted conformations, altered residues network and affected drug binding site which led to malfunction of mutant proteins. Hence, the study provides the role of CYP2C19 gene polymorphisms in susceptibility to CML population and explored the molecular basis of malignancies caused which may aid in the development of precise medicine or adjusting the drug dosages so as to reduce the chemotherapeutic side effects. Communicated by Ramaswamy H. Sarma